Diversity of Ceratocystis fimbriata causing canker and wilt disease on Cupressus sempervirens (Italian cypress) in Indonesia - RAHMAT PRATAMA; SUWANDI SUWANDI; AHMAD MUSLIM; MULAWARMAN MULAWARMAN (Society for Indonesian Biodiversity, 2025)
Abstract. Pratama R, Suwandi S, Muslim A, Mulawarman. 2025. Diversity of Ceratocystis fimbriata causing canker and wilt disease on Cupressus sempervirens (Italian cypress) in Indonesia. Biodiversitas 26: 278-287. In 2022-2023, new diseases were observed on Cupressus sempervirens in South Sumatra, Indonesia, with the disease incidence increasing from 17.6% to 26.5% in 2023. Initial symptoms, included stem cankers, black lesions on sapwood and vascular tissue, discoloration and partial wilting of leaves, and eventual complete drying, leading to plant death. The objective of this study was to isolate and identify the fungal pathogen causing wilt disease in C. sempervirens trees using morphological characterization and DNA sequencing. In 2022-2023, a disease survey was conducted in six districts of South Sumatra. The results showed that six out of ten locations were infected, with disease incidence ranging from 4.1% to 17.6% in 2022, increasing to 2% to 26.5% in 2023. Pathogen identification employed a polyphasic approach, combining morphological and molecular characteristics from specific genomic regions (the internal transcribed spacer (ITS) and ?-tubulin). Both the morphological features (including a globose base with a long neck-ended tip with ostiolar hyphae, cylindrical conidia, and hat-shaped ascospores) and phylogenetic analysis identified the isolates as Ceratocystis fimbriata. ITS gene sequences indicated that all the isolates belonged to the ITS5 haplotype. In pathogenicity test, pathogen caused mortality in C. sempervirens, Acacia mangium, and Artocarpus heterophyllus plants. The implications of these findings are significant, as they can potentially lead to the development of effective control measures. To our knowledge, this is the first report of Ceratocystis spp. causing wilt disease on C. sempervirens in South Sumatra.